2011
DOI: 10.1590/s0104-11692011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems and social support: Frailty in a Brazilian Elderly Multicenter Study

Abstract: This study identifies relationships among the quality of perceived social support and sleep problems and napping habits in community-dwelling elderly. This study is part of a larger multicenter project entitled "Frailty in Brazilian Elderly Individuals", conducted in 17 Brazilian cities. A total of 498 elderly individuals capable of participating in interviews and free of cognitive deficits or functional impairment were found. The following instruments were used in data collection: Questionnaire addressing soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 18 publications
4
26
0
2
Order By: Relevance
“…Costa et al [12] suggested that older adults with a lower score on the Interpersonal Support Evaluation List had increased sleep onset latency or nonrestorative sleep. A longitudinal study also found older adults, who felt subjectively lonely in the past, complained of more severe insomnia [13] .…”
Section: Social Isolation and Sleep Disturbancementioning
confidence: 99%
“…Costa et al [12] suggested that older adults with a lower score on the Interpersonal Support Evaluation List had increased sleep onset latency or nonrestorative sleep. A longitudinal study also found older adults, who felt subjectively lonely in the past, complained of more severe insomnia [13] .…”
Section: Social Isolation and Sleep Disturbancementioning
confidence: 99%
“…Empirically, Costa, Ceolim, and Neri () noted that older adults who had reported having sleep problems also reported having received lower levels of social support than those who did not report such sleep problems. In particular, older adults are more likely to experience social isolation or loneliness than younger adults are, due to certain inevitable life events, such as retirement and bereavement.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, we emphasize: quantitative reduction of deep sleep stages; reduction of the threshold for waking up due to noise associated with the quantitative increase in the superficial sleep; higher latency to sleep onset, increased daytime naps; reduction of the total nocturnal sleep duration; high number of transitions from one stage to another and to wakefulness; higher frequency of respiratory disturbances during sleep (3) .…”
Section: Introductionmentioning
confidence: 99%